Riau Regional Government Collaboration In The Implementation Of The P4gn National Action Plan - Dewi O. Eka Putri; Ichsan Malik; I. Gede Sumertha; Pujo Widodo; Herlina J. Saragih (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Indonesia is currently facing quite serious challenges in terms of the abuse of narcotics and illegal drugs. In general, narcotics and psychotropic substances can be used as medicinal ingredients in the medical field and in the development of science. The effects of this dependence can result in death. Not only that, other aspects such as moral and social are also affected by narcotics abuse. One of the biggest problems in Riau is the high circulation of drugs coming from abroad. The high distribution of drugs is influenced by various factors, in this case, geographical and demographic conditions in Riau. Based on the identification of drug-handling problems in Riau Province that have been explained, this paper has the objectives of, among others, analyzing efforts to implement P4GN, especially in the context of tackling drug trafficking and abuse in Riau Province; and analyze efforts to implement P4GN in Riau from a national security perspective. Collaborative governance focuses on the voluntary aspects of collaborative practice. From the voluntary aspect is expected that every actor involved can work optimally to achieve goals in the effort to implement the Prevention and Eradication of Drug Trafficking (P4GN) in Riau Province. With clear regulations and awareness of the importance of saving the nation's generation from the dangers of drugs, empirically the gray zones at the functional and operational levels can be mapped to the fullest so that the realization of a Drug-Clean Indonesia can be realized.